2022
DOI: 10.1002/asi.24646
|View full text |Cite
|
Sign up to set email alerts
|

How do properties of data, their curation, and their funding relate to reuse?

Abstract: Despite large public investments in facilitating the secondary use of data, there is little information about the specific factors that predict data's reuse. Using data download logs from the Inter-university Consortium for Political and Social Research (ICPSR), this study examines how data properties, curation decisions, and repository funding models relate to data reuse. We find that datasets deposited by institutions, subject to many curatorial tasks, and whose access and preservation is funded externally a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…In a mixed methods study, Melero & Navarro‐Molina looked at data sharing and reuse in the food science & technology field and found that the majority of respondents believed that it is labor intensive to make their data reusable by others [ 6 ]. Hemphil et al concluded that the more curation work done on a dataset such as adding metadata and providing more context on how the data was collected, the more the data was reused [ 7 ]. In a focus group study led by Johnston et al in 2016, they found that while those researchers felt that curation was important, only 18% of the researchers were satisfied with the curation services they received and identified several important data curation activities that libraries could develop or better advertise [ 3 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In a mixed methods study, Melero & Navarro‐Molina looked at data sharing and reuse in the food science & technology field and found that the majority of respondents believed that it is labor intensive to make their data reusable by others [ 6 ]. Hemphil et al concluded that the more curation work done on a dataset such as adding metadata and providing more context on how the data was collected, the more the data was reused [ 7 ]. In a focus group study led by Johnston et al in 2016, they found that while those researchers felt that curation was important, only 18% of the researchers were satisfied with the curation services they received and identified several important data curation activities that libraries could develop or better advertise [ 3 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Producers want to be credited when others use their data products for the effort involved in creating and sharing them [32]. To help ensure data are properly cited, producers can provide data citation guidance that mimics article citations by including author names, year, title of the data source, repository name, and unique persistent identifiers for shared artifacts [33].…”
Section: Background Data Producer Research Processmentioning
confidence: 99%
“…Through historical efforts, tasks and procedures have been developed in these fields to implement systematic data curation [ 12 ]. With the increasing reliability and interpretability of research data, the research style of reusing others’ research data is becoming the norm [ 13 ].…”
Section: Introductionmentioning
confidence: 99%